Disappearing - California c. 1970 Bas Jan Ader, Chris Burden, Jack Goldstein - Kaiser, Philipp 1972- (Modern Art Museum of Fort Worth, 2019)
"The artists Bas Jan Ader, Chris Burden, and Jack Goldstein shared a common interest in themes of disappearance in their works in Southern California around 1970. This book accompanies an exhibition by the same title, which reveals a fascinating intersection between these major figures as they respond to cultural pressures like the Vietnam War, conceptual art, and the rise of feminism"--
Impressum: This book was published on the occasion of the exhibition Disappearing-California, c. 1970: Bas Jan Ader, Chris Burden, Jack Goldstein, curated by Philipp Kaiser, with assistance from Jamin An, and organized by the Modern Art Museum of Fort Worth, on view May 10 to August 11, 2019
Keywords: Ader, Bas Jan -- 1942-1975; Burden, Chris -- 1946-2015; Goldstein, Jack -- 1945-2003; Ader, Bas Jan / 1942-1975 / Exhibitions; Burden, Chris / 1946-2015 / Exhibitions; Goldstein, Jack / 1945-2003 / Exhibitions; Ader, Bas Jan / 1942-1975; Burden, Chris / 1946-2015; Goldstein, Jack / 1945-2003; Performance art / California, Southern / Exhibitions; Absence in art / Exhibitions; ART / Individual Artists / Monographs; ART / Performance; ART / History / Contemporary (1945-); Performance art; California, Southern; Exhibition catalogs; Ausstellungskatalog -- Modern Art Museum of Fort Worth -- 10.05.2019-11.08.2019 -- Fort Worth, Tex.; Bildband